Investigating the role of sesamol in promoting the healing of diabetic wounds by analyzing molecular expression patterns in human diabetic dermal fibroblasts. - Beegum, Fathima; P V, Anuranjana; George, krupa thankam; K P, Divya; Begum, Farmiza; Krishnadas, Nandakumar; Rekha R Shenoy (Creative Pharma Assent, 2024)
Background: Sesamol (3,4-methylenedioxyphenol) is one of the plant compounds tested in vivo for diabetic wound healing, normal wound healing, and dexamethasone-induced delayed wound healing. Elucidation of mechanisms underlying the wound healing effect of sesamol through modulation of various molecular and cellular pathways is the crux of this paper. Objectives: The objective of the current work was to uncover the mechanism of sesamol underlying the treatment of diabetic wounds using gene expression analysis. Methods: The cytotoxicity assay was performed using an SRB colorimetric assay, from which two doses were selected for further studies. The expression of various molecular markers was performed using RT-PCR. Results: An SRB assay was carried out to identify the safe concentration of molecules in HDDF cell lines. Two doses that showed more than 80 % viability were selected and used for gene expression analysis. It was observed that sesamol enhanced the expression of VEGF, TGFβ, AKT, JNK, ERK, and TIMP3 significantly (P≤0.001, P≤0.05, P≤0.001, P≤0.0001) when compared to control and significantly (P≤0.0001) downregulated the expression of MMP2, MMP-9 when compared to control, which promote wound healing in diabetes. The migration studies also showed a significant increase when compared to the control. Conclusion: Sesamol (SM) is a promising molecule that can accelerate wound healing in diabetes by modulating different markers involved in the process.